Comparative Performance of Two Different Biofertilizers in Acidic and Alkaline Soils on Okra Growth (Journal of the Asiatic Society of Bangladesh, Science, 2025)
The present study evaluates the effects of two different types of biofertilizers on the growth of okra (Abelmoschus esculentus) following completely randomized design with three treatments (control, vermicompost, trichocompost) and three replications using acid soil (pH 4.77) and alkaline soil (pH 7.87) The results showed partial (pH 5.9) and complete (pH 6.4) neutralization of soil acidity by trichocompost and vermicompost whereas pH increased in alkaline soil but EC decreased significantly by both treatments. Besides, total OC, total N, total P, total K, total S all increased significantly (P